Canal and culvert tables with explanatory text and examples - Jackson, Lowis D'A (W.H. Allen, 1884)
With tabulated information on canals and culverts, to aid the engineering of such, this book was originally produced at the behest of the Government of India.
Keywords: Canals -- Design and construction -- Tables.; Culverts -- Hydrodynamics -- Tables.; elektronické knihy; electronic books